Pendampingan Santri dalam Giat Literasi di Pondok Pesantren Assunniyyah Kencong Jember - Furoidah, Asni; Mannan, Ahmad Mizan Rosyadi Abdul Jalil; Hamdi, Muhammad (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Islamic boarding schools are Islamic educational institutions that have a great contribution to the development of literacy. A student is equipped with knowledge so that he can explore the potential in himself to create a written work. The purpose of this assistance is to increase the potential of students in literacy activities and encourage students to continue to work. This method of mentoring uses the community based participatory research (CBPR) method to find the potential of students in developing literacy at the Assunniyyah Kencong Jember Islamic Boarding School which has now entered the industrial era 4.0. This research data was obtained through direct observation and documentation studies to the students. As a result of this assistance, students can increase their literacy potential and can produce a written work according to  the passion of each student. From the description above, it can be concluded that students have the potential to be literate among Islamic Boarding Schools, but they need special assistance so that their writing can be developed so that it produces a written work.